"A child, a tree": Challenges in building collaborative relations in a community research project in a Kenyan context. Issue 3 (September 2016) - Ahlberg, Beth Maina; Maina, Faith; Kubai, Anne; Khamasi, Wanjiku; Ekman, Marianne; Lundqvist-Persson, Cristina
This paper highlights the potential for basing participatory action research on priorities identified by communities. The case builds on a research project by the Social Science Medicine Africa Network (Soma-net) focusing on AIDS prevention among school youth in Kajiado in Kenya during 2003–2006. It became clear from that study just how complex it is to promote open communication on issues of sexuality considered critical for sexual health promotion. Towards the end of that study a spin-off in the form of a concept "a child, a tree" or tree planting evolved and the research thereafter continued as a partnership between the school community and the researchers. The focus then was on understanding how health promotion could be integrated into other aspects of community life. The concept and tree planting when implemented created a sense of ownership among the pupils largely because they were placed at the centre of the development activities. The story illuminates the nature of change developing in the course of the project, but also the challenges and complexity of creating and maintaining collaborative relations in the face of cultural and gender power dynamics and interventions imposed from outside the community.